Event study announcement of fraud and abnormal returns of BUMN companies - Umi Zahrotin Nafisa; Makaryanawati Makaryanawati; Haslinda Yusoff (Universitas Negeri Malang, 2023)
Abstract This study aims to determine the effect of fraudulent financial reporting of BUMN on abnormal returns. This study is important because most of the research examining these events has been conducted in developed markets. This study uses an event study approach with a window period of five days before and five days after the incident. By using the purposive sampling method, five BUMN companies that were reported to have committed the fraudulent in 2019 was selected in this study. The result shows that the incident of fraudulent financial report announcements does not significantly affect abnormal returns. This finding shows that the investors reaction the fraudulent news be not significant. This concludes that the news of fraudulent BUMN companies is not strong enough to influence investment decisions in the capital market. The results of this study are useful for investors in considering investment decisions in state-owned companies because they have fundamentally strong capital, so investors feel safe to invest. The results of this study contribute to the literature by adding new insights about fraud announcement events in BUMN. The results of this study also support the signal theory concept because investors respond to the second and third events as bad signalsAbstrak Penelitian ini bertujuan untuk mengetahui pengaruh peristiwa pengumuman kecurangan BUMN terhadap abnormal return. Penelitian inipenting untuk dilakukan karena sebagian besar penelitian yang mengkaji peristiwa tersebut dilakukan di pasar negara maju. Penelitian ini menggunakan pendekatan event study dengan periode jendela lima hari sebelum dan lima hari setelah peristiwa. Dengan menggunakan metode purposive sampling, lima perusahaan BUMN yang diberitakan melakukan kecurangan pada tahun 2019 menjadi sampel dalam penelitian ini. Hasilnya menunjukkan bahwa peristiwa pengumuman kecurangan tidak berpengaruh secara signifikan terhadap abnormal return. Temuan ini menunjukkan bahwa reaksi investor atas berita kecurangan tidak signifikan. Artinya berita kecurangan perusahaan BUMN tidak cukup kuat untuk memengaruhi keputusan investasi di pasar modal. Hasil penelitian ini bermanfaat bagi investor dalam mempertimbangkan keputusan investasi di perusahaan BUMN karena memiliki modal yang kuat secara fundamental, sehingga investor merasa aman untuk beinvestasi. Hasil penelitian ini berkontibusi pada literatur dengan menambah wawasan baru tentang peristiwa pengumuman kecurangan di BUMN. Hasil penelitian ini juga mendukung konsep teori sinyal karena investor merespons peristiwa kedua dan ketiga sebagai sinyal buruk